SsODNet: Solar system Open Database Network - Berthier, J.; Carry, B.; Mahlke, M.; Normand, J. (Astronomy and astrophysics (Berlin), 2023)
Context. The sample of Solar system objects has dramatically increased over the last decade. The number of measured properties (e.g., diameter, taxonomy, rotation period, thermal inertia, etc.) has expanded even more quickly. However, this wealth of information is spread over a myriad of studies, with different designations reported per object. Aims. We provide a solution to the identification of Solar system objects based on any of their multiple names or designations. We also compile and rationalize their properties to provide an easy access to them. We aim to continuously update the database as new measurements become available. Methods. We built a Web Service, SsODNet , which offers four access points, each corresponding to an identified necessity in the community: name resolution ( quaero ), compilation of a large corpus of properties ( dataCloud ), determination of the best estimate among compiled values ( ssoCard ), and a statistical description of the population ( ssoBFT ). Results. The SsODNet interfaces are fully operational and freely accessible to everyone. The name resolver quaero translates any of the ~5.3 million designations of objects into their current and official designation. The dataCloud includes about 105 million parameters (osculating and proper elements, pair and family membership, diameter, albedo, mass, density, rotation period, spin coordinates, phase function parameters, colors, taxonomy, thermal inertia, and Yarkovsky drift) from over 3000 articles (updated continuously). For each of the known asteroids and dwarf planets (~1.2 million), a ssoCard that provides a single best-estimate for each parameter is available. The SsODNet service provides these resources in a fraction of second upon query. Finally, the extensive ssoBFT table compiles all the best estimates in a single table for population-wide studies.